نسبة المساهمة بعض القدرات التوافقية في أداء أهم المهارات الاساسية لدي لاعبي أكاديميات كرة القدم بأعمار (10- 12) سنة في محافظة اربيل - درويش, بإشراف: أ.د نوزاد حسين; رشيد, رشيد رحمان (Sulaimani Journal for Humanities, 2023)
1- Recognizing the values of some harmonic abilities among football academy players at the ages of (10-12) years. 2- Recognizing the values of the most important basic skills of football academy players aged (10-12) years. 3- Identifying the percentage of the contribution of some harmonic abilities and performance of the most important basic skills of football academy players aged (10-12) years. The theoretical and similar studies included: The concept of harmonic abilities, their types, components, importance and characteristics of the age group for ages (10-12) years. And the concept of anthropometries and their importance, the influencing factors and their conditions, the basic skills in football, as well as the presentation of a group of similar studies that were commented on in the light of the current study. The search procedures are: The researcher followed the approach in the style of survey studies and correlational relations. The research community was identified from the football players of Erbil Governorate academies for ages (10-12) years, numbering (7) academies, represented by (Prosk Academy - Erbil Academy - Qala Academy - Soran Academy - Harir Academy - Fastlink Academy, Galatasaray Academies) where (168) players were selected in a comprehensive inventory method, to obtain data related to the research. The researcher used the statistical method known as the ready-made statistical package (SSPS). As for the presentation, analysis and discussion of the results: The results were presented and the analysis discussed for the variables of harmonic abilities, anthropometrics and basic skills for the research tests, which amounted to (5) tests of harmonic abilities and (4) skill tests. Each of the harmonic capabilities variables are represented by (numbered circles, collecting scattered balls, shuttle runs 4 * 10m, turning and shooting, running between 5 pillars) explained in the dependent variable (handling, rolling, suppression and scoring) in football. The independent variables and the dependent variable, after obtaining the results, were discussed in a scientific manner supported by the sources to achieve the objectives of the research. In light of the results, the following conclusions were reached: 1- It was possible to identify the values of some harmonic abilities affecting the level of the accuracy test of basic skill performance in football among the research sample. 2- There is a statistically significant correlation between the values of some harmonic abilities the accuracy of basic football skills performance in the research sample. Find the percentage of the contribution of the independent and explanatory variables to the variables dependent on the research sample.